Flyaway - Christopher, Lucy (New York : Scholastic, 2013)
While visiting her father in hospital, thirteen-year-old Isla meets Harry, the first boy to understand her and her love of the outdoors. But Harry is ill, and as his health fails, Isla is determined to help him in the only way she knows how. Together they watch a lone swan struggling to fly on the lake outside Harry's window.
K
580
K
Keywords: Sick -- Juvenile fiction; Swans -- Juvenile fiction; Wildlife rescue -- Juvenile fiction; Families -- Juvenile fiction; Fathers and daughters -- Juvenile fiction